TPACK Tried and Tested: Experiences of Post-Secondary Educators During COVID-19 Pandemic - Manokore, Viola; Kuntz, Jeff (International journal for the scholarship of teaching and learning, 2022)
This article explores educators’ experiences during the rapid shift from face-to-face to emergency virtual remote teaching and learning as a result of the COVID-19 pandemic. One hundred and forty educators from a Canadian province completed a survey with Likert scale and open-ended questions designed to capture their application of technological pedagogical content knowledge (TPACK) during the pandemic. Data was collected during fall of 2020. More than 50% of the study participants reported that the quality of their practice declined as they shifted from face-to-face to remote teaching as a result of the pandemic. Educators’ descriptions of their virtual remote experiences were examined using Hutchings’ (2000) taxonomy of scholarship and inquiry questions as an analytic lens. The findings suggest that educators who were more comfortable with their TPACK had an easier transition to virtual remote teaching. Institutional support, students’ digital literacy/access, and overall wellbeing were also identified as factors that influenced educators’ overall experiences.